Biochemical compositional and technological characterizations of black and white myrtle (Myrtus communis L.) fruits - Hacıseferoğulları, Haydar (Springer-Verlag, 2011)
Biochemical and technological properties were determined in developing Myrtus communis L. fruits (myrtle) from Mersin to investigate potential uses. Completely ripe black and white fruits contained ash, crude protein, crude oil, water- and alcohol soluble extracts, tartaric, malic and citric acids, and minerals including Ca, K, P, Mg and Na. Proximate compounds (%) for black and white fruits were: 7.47 and 6.36 protein, 3.487 and 3.453 oil, 3.02 and 2.30 ash, 24.28 and 26.09 dry matter, respectively. Fruits were found to be rich in some minerals such as Ca (6719.88 mg/kg and 4676.14 mg/kg), K (22647.78 mg/kg and 18339.84 mg/kg), Mg (2145.19 mg/kg and 1408.88 mg/kg), Na (3336.16 mg/kg and 2976.59 mg/kg) and P (4336.07 mg/kg and 3927.4 mg/kg). Also, physical properties such as length (14.94 mm and 13.64 mm), mass (0.94 g and 0.94 g), geometric mean diameter (12.73 mm and 12.31 mm), sphericity (0.85 and 0.90), diameter (11.76 and 11.70), projected area (1.48 cm(2) and 1.65 cm(2)), kernel density (757.47 kg/m(3)and 752.09 kg/m(3)), porosity (41.41% and 39.05%), bulk density (426.50 kg/m(3) and 431.05 kg/m(3)), terminal velocity (8.42 m/s and 8.49 m/s), volume (1.32 mm(3) and 1.35 mm(3)), repture strenth (1.77 N and 2.06 N), static (0.26–0.33 and 0.20–0.28) and dynamic coefficient (0.22–0.29 and 0.17–0.24) of friction of black myrtle and white myrtle fruits species were measured at 75.72% and 73.91% moisture content levels, respectively. These results show that both myrtle fruits may be useful for the evaluation of dietary information in important food crops.